Concise, gram-scale synthesis of furo[2, 3-b]pyridines with functional handles for chemoselective cross-coupling. Issue 38 (17th September 2020) - O'Byrne, Sean N.; Eduful, Benjamin J.; Willson, Timothy M.; Drewry, David H.
Graphical abstract: Highlights: Furopyridines are increasingly important heterocycles in medicinal chemistry. Furopyridines can be utilized as hinge binders in kinases inhibitors. 4-Step novel synthetic route allows easy access to this heterocycle on gram scale. The chemoselective cross-coupling is achieved with high selectivity and yield. Abstract: A concise 4-step synthesis of furo[2, 3- b ]pyridines, with handles in the 3- and 5-positions for palladium mediated cross-coupling reactions, is described. The synthetic route has been optimized, with only one step requiring purification by column chromatography. The route is amenable to scale-up, and was successfully executed on a multi-gram scale. Furopyridines are of growing interest in medicinal chemistry, and this route should enable easy access to the core for structure-activity relationship (SAR) studies.